On the rheology and magnetization of dilute magnetic emulsion under small amplitude oscillatory shear - Abdo, Rodrigo Figueiredo (2023)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2023.